THE COMPLEX SENTENCE ACQUISITION BY FIVE YEARS OLD KINDERGARTEN STUDENTS - Resdilla Pratiwi; Lonni Nur Iffah Nasution; Winda Putri Ardina (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
This research deals with language acquisition. It aims to describe what types of complex sentences are produced by five years old Kindergarten students in their social interaction. The methodology of this research uses Qualitative Research where the researcher involved six kindergarten students of five years old in RA Fatayat Nahdhatul Ulama Batahan as data sources. The data of this research was obtained by using the naturalistic method by observing, making a conversation, recording, and taking notes. The result found that the Five years old kindergarten students already produced a noun clause, relative clause, and adverbial clause as subordinate clause or dependent clause to modify or give more explanation about the main clause or independent clause to produce complex sentences. And they also used a coordinating conjunction and subordinating conjunction to join the dependent clause to the independent clause, or they just used an intonation to separate between dependent clause from independent clause.